Macroprudential and Monetary Policy Interactions in a DSGE Model for Sweden - Chen, Jiaqian (IMF Working Papers; Working Paper ;, 2016)
We analyse the effects of macroprudential and monetary policies and their interactions using an estimated dynamic stochastic general equilibrium (DSGE) model tailored to Sweden. Households face a ceiling on their loan-to-value ratio and must amortize their mortgages. The government grants mortgage interest payment deductions. Lending rates are affected by mortgage risk weights. We find that demand-side macroprudential measures are more effective in curbing household debt ratios than monetary policy, and they are less costly in terms of foregone consumption. A tighter macroprudential stance is also found to be welfare improving, by promoting lower consumption volatility in response to shocks, especially when using a combination of macroprudential instruments.